A study on the awareness of bumiputra towards the partial concept of financial planning in terms of investment in unit trust funds provided by PNB / Yusaini Yahya - Yahya, Yusaini (Faculty of Business and Management, 2003)
'Permodalan Nasional Berhad' or PNB was incorporated on March 17, 1978 with the role as one of the government's instrument in proceeding with the execution of the New Economic Policy. The goal is to promote share ownership in the corporate sector among the Bumiputra, and develop opportunities for suitable Bumiputra professionals to participate in the creation and management of wealth.